1984
DOI: 10.1103/physrevb.30.3629
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam-induced epitaxial regrowth of amorphous layers in silicon on sapphire

Abstract: A neon ion beam has been used to regrow epitaxially a -1700-A-thick amorphous surface layer in silicon on sapphire at low temperatures. The damaged layer was produced by implanting 80-keV silicon ions to a dose of 2)&10' ions/cm at room temperature. The channeling technique with 315-keV protons was used to investigate the depth distribution of the damage, and disorder depth profiles were extracted from the backscattering spectra using calculations based on multiplescattering theory. The epitaxial regrowth was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…This issue will be addressed later. The abovementioned conclusions were also confirmed by other experimental results Linnros et al, 1984Linnros et al, , 1985Miyao et al, 1986;Williams et al, 1985). For instance, Linnros (Linnros et al, 1985) reported a clear experimental evidence of a linear dependence of the ion-induced recrystallization rate on the nuclear energy loss.…”
Section: Influence Of the Beam Parameters In The Ibiec Processsupporting
confidence: 78%
See 2 more Smart Citations
“…This issue will be addressed later. The abovementioned conclusions were also confirmed by other experimental results Linnros et al, 1984Linnros et al, , 1985Miyao et al, 1986;Williams et al, 1985). For instance, Linnros (Linnros et al, 1985) reported a clear experimental evidence of a linear dependence of the ion-induced recrystallization rate on the nuclear energy loss.…”
Section: Influence Of the Beam Parameters In The Ibiec Processsupporting
confidence: 78%
“…For instance, at 250 °C the ion-induced growth rate is 0.07 Å/s while, an extrapolation of the thermal data gives a rate of only 10 -10 Å/s. Furthermore, in the temperature range shown, the IBIEC presents an Arrhenius-like temperature dependence with an apparent activation energy of (0.32  0.05) eV as also demonstrated by several other experiments Linnros et al, 1984;Williams et al, 1985).…”
Section: Temperature Dependencementioning
confidence: 61%
See 1 more Smart Citation
“…An alternative method to conventional thermal annealing to restore the crystallinity of heavily damaged crystals is the use of the ion-beam induced epitaxial crystallisation (IBIEC) process [41][42][43]. It consists in bombarding the samples with ion species having an energy such that the slowing down is still dominated by nuclear collisions, but with an ion projected range quite deeper than the thickness of the defective layer.…”
Section: Swift Heavy Ion Beam Induced Epitaxialmentioning
confidence: 99%
“…Ion beam-induced epitaxial crystallisation (IBIEC) is a promising route to achieve solid phase epitaxial growth in silicon and other materials at considerably lower target temperatures [3][4][5][6][7][8][9] . IBIEC has advantages of low processing temperature and layer-by-layer crystallisation.…”
Section: Introductionmentioning
confidence: 99%